P477Myeloid PHD-2 deficiency leads to enlarged and fibrotic atherosclerotic plaques in mice. (15th July 2014) - Theelen, T L; Marsch, E; Demandt, J; Dinjens, C; Cleutjens, JP; Gijbels, MJ; Carmeliet, P; Daemen, MJAP; Sluimer, JC
Abstract: Purpose: Macrophage specific knockout of PHD-2 prolylhydroxylase domain protein 2 (PHD-2-/-), the crucial cellular oxygen sensor, increased anti-inflammatory M2 macrophages, angiogenesis and arteriogenesis in mice. As macrophages and angiogenesis are known to enhance progression of atherosclerotic plaques, we hypothesized that macrophage PHD-2-/- would increase plaque size and progression. Methods: LysMCre-low density lipoprotein receptor knockout (LDLR-/-) (control, n = 18) and lysMCre PHD-2fl/fl LDLR-/- mice (PHD-2-/-, n = 18) mice were fed a high cholesterol diet (0.25%) for 12 weeks to analyze atherosclerosis, MAC3+ macrophage content and CD31+ microvessel density in the aortic root. Collagen content was quantified using polarized light microscopy of sirius red stained plaques. Results: Plaque size was increased 40% in PHD-2-/- mice (361.1±19.1 10 3 μm 2 ) compared to control (215.9±13.5 10 3 μm 2 p<0.0001), despite a slight decrease in plasma cholesterol in PHD-2-/- mice vs. control (31.43±1.04 vs. 35.03±1.18 mmol/l resp, p<0.05). Necrotic/lipid core content was similar (12.5±0.66 vs. 12.77±1.02 % of plaque resp.), whereas PHD-2-/- reduced macrophage content by 37% (24.2±1.86 vs. 38.2±3.59 % of Mac-3+ area p<0.01). Although PHD-2-/- plaques more frequently contained erythrocytes (53% vs 17% of control, p<0.05), suggestive of increased plaque angiogenesis, only two out of 18 PHD-2-/- mice showed intraplaque angiogenesis vs none in the control. Likewise, adventitial microvessel density was similar (0.039 vs 0.036 vessels/mm 2 ). Interestingly, plaque collagen content was increased 22% in PHD-2-/- vs control (39.34±0.96 vs. 30.73±1.43 % sirius red resp., p<0.0001) with a collagen subtype shift towards more condensed, mature fibers in PHD-2-/- mice. Finally, body weight, serum triglycerides, and hematopoiesis (flow cytometry of T cells, B cells, monocytes, and granulocytes in blood, spleen and lymphe nodes) did not differ. Conclusions: In conclusion, macrophage PHD-2-/- led to larger plaques with more fibrosis and less inflammation. Thus PHD-2-/- improved plaque stabilization, and PHD2 inhibition may therefore provide a new therapeutic avenue to prevent plaque destabilization.